Assessing Compassion in Korean Population: Psychometric Properties of the Korean Version of Sussex-Oxford Compassion Scales - Kim, Jiyoung; Seo, Jang-Won (Frontiers in Psychology, 2021)
A newly developed scale, the Sussex-Oxford Compassion Scale (SOCS) measures compassion for others and the self-based on an empirically supported five-elements definition of compassion: (a) recognizing suffering; (b) understanding the universality of suffering; (c) feeling for the person suffering; (d) tolerating uncomfortable feelings; and (e) motivation to act/acting to alleviate suffering. This study aimed to validate a Korean version of SOCS in a Korean adult sample. We administered the Sussex-Oxford Compassion Scale for Others (SOCS-O), the Sussex-Oxford Compassion Scale for the Self (SOCS-S), and other self-report measures of mindfulness, self-compassion, compassionate love, wellbeing, interpersonal reactivity, and mental health problems to analyze their psychometric properties. The findings support the five-factor hierarchical structure for the SOCS-O and SOCS-S, and as well as both scales’ adequate psychometric properties of measurement invariance, interpretability, internal consistency, floor/ceiling effects, and convergent/discriminant validity.